OP0265 Fever of Unknown Origin (FUO) and Inflammation of Unknown Origin (IUO): Is 18F-FDG-PET/CT A Useful First Line Diagnostic Strategy?. (15th July 2016) - Schoenau, V.; Vogel, K.; Engelbrecht, M.; Schmidt, D.; Kuwert, T.; Manger, B.; Schett, G.
Abstract : Background: Fever of unknown origin (FUO) and inflammation of unknown origin (IUO) are rare but diagnostically challenging clinical problems. Because of the abundance of differential diagnoses, a generally accepted diagnostic guideline has not yet been established. Besides a thorough medical history, physical examination, and laboratory testing, imaging techniques are important tools in the diagnostic workup of FUO and IUO. In the last few years, 18 F-FDG-PET/CT has been found to be a suitable diagnostic tool for FUO/IUO, as it is able to detect inflammatory and malignant processes with a high spatial resolution. Objectives: The present study is carried out at to quantify the utility of 18 F-FDG-PET/CT for the diagnosis of FUO and IUO. The study, moreover, evaluates special clinical markers, that increase the possibility of diagnosing FUO or IUO with a 18 F-FDG-PET/CT. Methods: All patients presenting with FUO or IUO at the University Clinic of Erlangen between 2007 and 2015 were clinically documented and subjected to 18 F-FDG-PET/CT scanning. 18 F-FDG-PET/CT scans were considered positive when a focal uptake of the tracer was detected additionally to the standard areas of physiological tracer uptake. 18 F-FDG-PET/CT results were compared to the final diagnosis and classified as helpful or non-helpful in establishing the final diagnosis. Multivariate logistic regression was used to identify clinical parameters that correlated with a helpful 18 F-FDG-PET/CT in patients with and without FUO as well as in patients with and without IUO. Results: Of the 240 patients enrolled 72 presented with FUO, 142 with IUO and 26 did not fulfill FUO or IUO criteria. 235 patients were included in the multivariate logistic regression model. Final diagnosis was established in 190 patients (79.2%). In 136 (56.7% of all patients and 71.6% of the patients with a diagnosis), the 18 F-FDG-PET/CT was helpful in finding the diagnosis. The chance was higher in patients without fever (p=0.003), those aged >50 years (p=0.002; p=0.005, respectively) and those with a CRP level >30 mg/dl (p=0.003; p=0.008, respectively). Conclusions: Our study shows that if the standard diagnostic tests (laboratory, chest x-ray and abdominal ultrasound) did not identify the cause of FUO/IUO, 18 F-FDG-PET/CT scanning should be applied in the early stage of the diagnostic process. An early use of an 18 F-FDG-PET/CT is especially helpful to establish a final diagnosis in patients with an elevated C-reactive protein and age over 50 years. Disclosure of Interest: None declared